Evaluating Socratic inquiry, reflection and argumentation as strategies for critical thinking - Malape, Glen T.; Makhene, Agnes; Mutava, Eunice (Curationis (Pretoria), 2025)
Background Rapid technological advancements, the ageing population and the complex disease management processes significantly change the healthcare environment, fostering a dire need for nurses who can think critically. Critical thinking (CT) is foundational to clinical competency. However, there is a shortage of evidence on the identification of the most suitable pedagogies to promote CT. Objectives This article aims to implement and evaluate the effectiveness of Socratic inquiry, reflection and argumentation as CT facilitation strategies in nursing education. Method A quantitative, quasi-experimental, pretest-post-test research design was used. Thirty-two student nurses were selected through convenience sampling. Data were gathered using the Holistic Critical Thinking Scoring Rubric (HCTSR) and analysed through descriptive and inferential statistics, using the SPSS software version 28.0. Results The results showed that the three strategies were successful in promoting CT. Overall, Socratic inquiry, reflection and argumentation were effective in enhancing students’ CT; five of the six domains of CT saw a statistically significant improvement following the implementation of the three facilitation strategies. Conclusion Socratic inquiry, reflection and argumentation are effective pedagogies for the facilitation of nursing students’ CT. Evidenced by improved post-test means of all CT attributes and statistically significant improvements in five of the six CT competencies. Contribution The findings of this study demonstrate the effectiveness of Socratic inquiry, reflection and argumentation in enhancing nursing students’ CT. The study also makes recommendations on the improvement of nursing practice, education and policy development, to foster a system that will create nurses who can think critically to enhance patient outcomes.